Technology and Disasters: The Evolution of the National Emergency Tele-Critical Care Network. Issue 7 (17th June 2021) - Pamplin, Jeremy C.; Scott, Benjamin K.; Quinn, Matthew T.; Little, Jeanette R.; Goede, Matthew R.; Pappas, Peter A.; Jolly, B. Tilman; Hipp, Sean J.; Colombo, Christopher J.; Davis, Konrad L.
Abstract : Supplemental Digital Content is available in the text.